26.6k views
5 votes
What do i have to do?

What do i have to do?-example-1
User Dus
by
4.6k points

2 Answers

4 votes

Answer:

136

Explanation:

Given

h + k² - j ( substitute the given values into the expression ) , that is

3 + 11² - (- 12)

= 3 + 121 + 12

= 136

User Medina
by
5.1k points
2 votes

Answer:

It is 136

Explanation:


h + {k}^(2) - j

substitute respectively as in question:


= 3 + {(11)}^(2) - ( - 12)

open brackets:


= 3 + 121 + 12 \\ = 136

User Fergus Bown
by
4.8k points